2009
DOI: 10.1111/j.1439-0272.1994.tb00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterqides ureolyticus in men consulting for infertility

Abstract: A screening of 3196 semen analyses performed in our clinic from January 1986 to December 1990 revealed 314 (9.8%) patients whose semen was infected with Bacteroides ureolyticus. Investigating the relationship between the presence of B. ureobticus, the seminal microflora and the conventional semen parameters, we observed that the presence of this micro-organism in the semen was coupled (1) to an increased presence of Enterococcus species, (2) to an increased number of short-tailed spermatozoa and epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…These results are supported by the strong adhesion of these bacterial strains to the surface of the sperm head, midpiece, and principal piece, as has been recently documented [16]. In turn, the link between B. ureolyticus and male infertility was discussed long ago in the literature [43]. Interestingly, our earlier in vitro experiments indicated that free radical species mediate the cytotoxic effect of these bacteria on spermatozoa as a consequence of lipid peroxidative damage to the membranes [20].…”
Section: Discussionsupporting
confidence: 60%
“…These results are supported by the strong adhesion of these bacterial strains to the surface of the sperm head, midpiece, and principal piece, as has been recently documented [16]. In turn, the link between B. ureolyticus and male infertility was discussed long ago in the literature [43]. Interestingly, our earlier in vitro experiments indicated that free radical species mediate the cytotoxic effect of these bacteria on spermatozoa as a consequence of lipid peroxidative damage to the membranes [20].…”
Section: Discussionsupporting
confidence: 60%
“…Earlier studies regarding semen infection with B. ureolyticus suggested participation of this strain or its toxins in the reduction of normal sperm morphology, increased number of epithelial cells in ejaculate, and a change in biochemical semen characteristics (40). Thus, the results indicate that anaerobic colonization of the male genital tract can have a direct effect on sperm function, with negative consequences for male fertility, owing to the membrane peroxidation.…”
Section: Figurementioning
confidence: 83%
“…In our previous study, we demonstrated that experimental infection of semen with B. ureolyticus resulted in oxidative damage including lipid sperm membrane peroxidation (Fraczek et al ., ). Our previous results and the present data increased our knowledge of toxic effects of B. ureolyticus towards spermatozoa and indicated that anaerobes’ invasion, colonization or infection of the male genital tract may have a symptomatic effect on sperm structure with negative consequences for male infertility owing to molecular alterations in the sperm membranes (Balmelli et al ., ).…”
Section: Discussionmentioning
confidence: 97%